Morfometria de lagoas marginais da bacia do alto Paraguai : relação com a estrutura e dinâmica das comunidades de peixes no Pantanal de Cáceres-MT - Moura, Nelson Antunes de (2010)
Most ecological studies of tropical fishes involve limnology related to reproductive behavior, feeding and migration. This work is an attempt to consider, in the area of fish ecology, a new approach that involves addition of limnological variables, environmental variables morphometric and morphologic environment and determine whether, beyond the flood pulse, these characteristics determine the community structure fish in the wetland. Were chosen ten ponds, regionally called "bays" on the banks of the rivers Paraguay, Paraguaizinho, and Sepotuba Cabaçal. Their morphology and physical and chemical variables of water were measured. A sampling of the ichthyofauna was done in three sampling points in each pond using trawl 3mm between us, 2.5 x25m long. Species richness was analysed using indices of Margalef and Minhinicke. We used multivariate analysis to determine the environmental variables that contributed in determining the structure of fish communities. Correspondence Analysis showed that the major groups of fishes related to species richness in two main groups: periods of low water, drought and flood, and the flood period. The abundance showed clustering contrast, the higher observed during periods of low water, drought and flood and the lowest found during the flood. Results of discriminant analysis demonstrated that the lakes are listed in four categories, depending on the degree of similarity of environmental characteristics. In each category groupings were more strongly related collection period than the limnological and morphometric analysis. However, the group found in the discriminant analysis, the lake VI (Ximbuva) shown by the rounded morphology and the morphometric values smaller lake VIII (the right bank of the river Cabaçal), show that the two are related to the structure of fish community wetland at the local level, while the flood pulse events determined the regional level.